2009
DOI: 10.1038/hr.2009.77
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin accelerates ischemia-induced angiogenesis through AMP-activated protein kinase

Abstract: Statins exert pleiotropic effects on the cardiovascular system, in part through an increase in nitric oxide (NO) bioavailability. In this study, we examined the role of pravastatin in ischemia-induced angiogenesis. Unilateral hindlimb ischemia was surgically induced in C57BL/6J mice. Phosphorylation of AMP-activated protein kinase (AMPK), acetyl-CoA carboxylase (ACC) and endothelial NO synthase (eNOS) was increased in ischemic tissues. Furthermore, mice treated with pravastatin showed higher increases in phosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 37 publications
3
25
0
Order By: Relevance
“…Notably, although the AMPK inhibitor suppressed the endogenous Akt phosphorylation, the Akt inhibitor had no effect on the endogenous phosphorylation of AMPK in MMVECs. The present data suggest that apelin-13 exerts pro-angiogenic effects in MMVECs through the modulation of AMPK and Akt signaling and the activation of eNOS, which is in accordance with previous studies (28,29,30). A study by Nagata et al (11) demonstrated that AMPK did not exhibit an effect on endothelial cell migration, tube formation and NO production under normoxia, which suggests that further in vitro and in vivo studies are required to gain a greater understanding of the role of endothelial cell AMPK in angiogenesis.…”
Section: Discussionsupporting
confidence: 80%
“…Notably, although the AMPK inhibitor suppressed the endogenous Akt phosphorylation, the Akt inhibitor had no effect on the endogenous phosphorylation of AMPK in MMVECs. The present data suggest that apelin-13 exerts pro-angiogenic effects in MMVECs through the modulation of AMPK and Akt signaling and the activation of eNOS, which is in accordance with previous studies (28,29,30). A study by Nagata et al (11) demonstrated that AMPK did not exhibit an effect on endothelial cell migration, tube formation and NO production under normoxia, which suggests that further in vitro and in vivo studies are required to gain a greater understanding of the role of endothelial cell AMPK in angiogenesis.…”
Section: Discussionsupporting
confidence: 80%
“…AMPK has been shown to be crucial not only for regulation of metabolic homeostasis but also for regulation of homeostasis in the cardiovascular system via activating eNOS (35). Indeed, it has been reported that an HMG-CoA reductase inhibitor (36), fenofibrate (37) and adiponectin (38) enhance angiogenesis in response to hindlimb ischemia through activation of the AMPK-eNOS signaling pathway. Previous experiments on genetic or pharmacological inhibition of AMPK activity showed significant reduction in phosphorylation of eNOS, leading to decrease in NO production (39).…”
Section: Hcii Restores Thrombin-induced Reduction Of Enos Phosphorylamentioning
confidence: 99%
“…The hindlimb blood flow was assessed under anesthesia with sodium pentobarbital (50 mg/kg, i.p.) using a laser Doppler blood flow (LDBF) analyzer (Moor LDI; Moor Instruments, Devon, UK) before and immediately after surgery and on postoperative days 4, 7, 14, 21 and 28, as previously described 11,12) . The LDBF analysis was performed before each treatment session on days 4, 7, 14 and 21 and 24 hours after the last treatment.…”
Section: Laser Doppler Blood Flow Analysismentioning
confidence: 99%
“…Unilateral hindlimb ischemia was induced under anesthesia with sodium pentobarbital (50 mg/kg intraperitoneally (i.p. )), as previously described 7,[11][12] . Mixed air dry mist (AM) and CO2 mist (CM) was generated using a dry mist production unit (Advance Biotron Co., Ltd., Tokyo, Japan) 10) .…”
Section: Introductionmentioning
confidence: 99%